Site selection for the development of organic farming for conservation purposes in the upstream of Air Bengkulu watershed, Bengkulu - Lovita, V.; Sulistyo, B.; Listyowati, E. A. (IOP Publishing Ltd, 2022)
Awareness of the dangers posed by the use of synthetic chemicals in farming attracts attention. The development of organic agriculture requires a suitable location. However, sometimes, suitable land is very limited. This study aims to select the site for the development of organic agriculture, as well as to function in overcoming the existence of critical land, especially in the Upstream of Air Bengkulu Watershed, Bengkulu. The research method carried out is by compiling a Map of Conservation Activity Plan (CAP) based on a model developed by the then Ministry of Environment and Forestry. Maps used for input to CAP are EHL (Erosion Hazard Level), Soil Depth, Slope, Population Pressure, and the Recommended Landuse. From the CAP Map, the sites that are estimated to be used for organic farming development locations will be obtained. Results show that the sites for CAP to support organic farming is divided, broadly, into 2 categories: (1) mixed cultivation, minimum tillage, planting of ground cover, management of organic matter and application of agroforestry covers 9.32 in Semidang Lagan and Karang Tinggi District, and (2) mixed cropping, minimum tillage, ground cover planting, organic matter management, permanent vegetation and application of agroforestry covers 38.79 in Taba Penanjung District, Bajak Dua, Jambu and Rindu Hati Village. While 51.89 of the study area in Taba Penanjung District should be used for protected area. © Published under licence by IOP Publishing Ltd.